The many faces of precision (Replies to commentaries on “Whatever next? Neural prediction, situated agents, and the future of cognitive science”) - Clark, Andy (Frontiers in Psychology, 2013)
An appreciation of the many roles of ‘precision-weighting’ (upping the gain on select populations of prediction error units) opens the door to better accounts of planning and ‘offline simulation’, makes suggestive contact with large bodies of work on embodied and situated cognition, and offers new perspectives on the ‘active brain’. Combined with the complex affordances of language and culture, and operating against the essential backdrop of a variety of more biologically basic ploys and stratagems, the result is a maximally context-sensitive, restless, constantly self-reconfiguring architecture.